On active grounds : agency and time in the environmental humanities - Boschman, Robert, 1961-; Trono, Mario, 1962- (Environmental humanities., 2019)
"On Active Grounds considers the themes of agency and time through the burgeoning, interdisciplinary field of the environmental humanities. Fourteen essays and a photo album cover topics such as environmental practices and history, temporal literacy, graphic novels, ecocinema, ecomusicology, animal studies, Indigeneity, wolf reintroduction, environmental history, green conservatism, and social-ecological systems change. The book also speaks to the growing concern regarding environmental issues in the aftermath of the 2015 Paris Climate Conference (COP21) and the election of Donald Trump in the United States. This collection is organized as a written and visual appeal to issues such as time (how much is left?) and agency (who is active? what can be done? what does and does not work?). It describes problems and suggests solutions. On Active Grounds is unique in its explicit and twinned emphasis on time and agency in the context of the Environmental Humanities and a requisite interdisciplinarity."--